Prevalence study of musculoskeletal disorder symptom among visual display terminal users / Noor Hidayu Abdullah - Abdullah, Noor Hidayu (2011)
Introduction: Ergonomic risk associated with activities involving Visual Display Terminal (VDT) could possibly increase among office workers due to length of work time. Common risks factors normally associated with VDT operations involve musculoskeletal disorders (MSDs) problem. Objective of this study is to determine the prevalence of MSDs symptoms and to associate muscular strength (pinch and grip strength) on wrist and finger muscular strength among VDT user. Methodology: The study was conducted among selected office staffs (n= 102) in a manufacturing factory located at Sangi, Selangor. This study is a cross-sectional study. The sampling data was collected using modified Nordic Musculoskeletal Disorder Questionnaire, interviews, body parts symptoms survey (SPSS) & photographs. Muscular strength (pinch and grip strength), were measured using JAMAR Hydraulic Hand Dynamometer & Hydraulic Pinch Gauge Strength Measurement. Analytical and descriptive statistical analysis was determined using Statistical Package for the Social Science (SPSS) version 18.0 was used in this study. Result: Found that there is an association for MSDs symptom between the VDT levels of usage (VDT users >4 / <4 hours/day) on upper body parts: neck, wrist, finger, elbow, forearms, upper & lower back and hip (p value<0.01 ), shoulders (p value<0.05), while for lower body'°'parts: lower legs, thigh & ankle (p value>0.05). Independent t-tests showed that there are significant different between grip strength (p value<0.01) and tip-pinch strength (p value<0.05) between VDT levels of usage (VDT users >4 / <4 hours/day), while there was no mean difference between keypinch strength (p value>0.05) and palmar-pinch strength (p value>0.05) between VDT levels of usage (VDT users >4 / <4 hours/day). However, the study found that, there was no association between the MSDs symptom on wrist/finger(p value>0.05) with grip and pinch strength in VDT usage for more than 4 hours per day. Conclusion: This study suggested that, the duration of VDT level of usage (VDT user > 4 hours/day working for at least 12 month) showed development of MSDs Symptom, indicating chronic ergonomic problems. There is a mean different between grip strength (p value<0.01) and tip-pinch strength (p value<0.05) between VDT levels of usage (VDT users >4 / <4 hours/day), indicate length of daily work may have MSDs linkage. On the other hand, there was no association between the MSDs symptom on wrist/finger (p value<0.05) among VDT user for more than 4 hours/day, indicating acute ergonomic problems. Solutions and recommendations derived from the study to reduce problems of MSDs among VDT users.